A polyurethane‐based nanocomposite biocompatible bone adhesive. Issue 6 (14th June 2012) - Schreader, Kevin J.; Bayer, Ilker S.; Milner, Derek J.; Loth, Eric; Jasiuk, Iwona
Abstract A novel polyurethane‐based foam‐like adhesive reinforced with nanosized hydroxyapatite (HA) particles was developed and investigated for bone‐to‐bone bonding applications in terms of mechanical adhesion and biocompatibility. The adhesive has a hierarchical structure with HA particles at the nanoscale level and pores at the micro‐scale level. This adhesive was tested mechanically in the three principal loading modes anticipated: shear, tension, and compression. Standard testing procedures were used when available. Tensile strength of primed adhesive showed a four‐fold increase in adhesion on unmodified bone and a nearly two‐fold increase in adhesion to primed bone as compared with the conventional bone cement. Biocompatibility was initially assessed in vitro using cell culture tests, which showed positive interaction with the adhesive. Then, a second biocompatibility test was performed using Xenopus laevis limbs to assess an in vivo response. The results indicated that the adhesive material produces a normal response consistent with control specimens. However, long‐term observations and tests with additional species are needed to demonstrate full biocompatibility. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2013